Innovation policy in a global economy - Archibugi, Daniele; Howells, Jeremy 1956-; Michie, Jonathan (Cambridge University Press, 1999)
Innovation Policy in a Global Economy concludes the successful sequence of books on Globalisation and Technology edited by Daniele Archibugi and Jonathan Michie, following Technology, Globalisation and Economic Performance (Cambridge University Press, 1997) and Trade, Growth and Technical Change (Cambridge University Press, 1998). This final volume argues that the opportunities offered by globalisation will only be fully realised by organisations which have developed institutions that allow for the transfer, absorption, and use of knowledge. Innovation Policy in a Global Economy is relevant for graduate and undergraduate courses in management and business, economics, geography, international political economy, and innovation and technology studies. Presenting original theoretical and empirical research by leading international experts in an accessible style, Innovation Policy will be vital reading for researchers and students and of use to public policy professionals
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Technological innovations / Economic aspects / Congresses; Technology and state / Congresses; Wirtschaft; Globalisierung; Innovationsförderung; Innovation; Internationalisierung; Technische Innovation; Konferenzschrift